Histories of infamy : Francisco López de Gómara and the ethics of Spanish imperialism - Roa-de-la Carrera, Cristián Andrés, 1969- (University Press of Colorado, 2005)
In Histories of Infamy, Cristián Roa-de-la-Carrera explores Francisco López de Gómara's (1511-ca.1559) attempt to ethically reconcile Spain's civilizing mission with the conquistadors' abuse and exploitation of Native peoples. The most widely read account of the conquest in its time, Gómara's Historia general de las Indias y Conquista de México rationalized the conquistadors' crimes as unavoidable evils in the task of bringing "civilization" to the New World.